Proyecto de factibilidad para la creación de una empresa procesadora de abono orgánico en base al estiércol de pollo y su comercialización en los cantones Balsas, Marcabelí, Piñas, Portovelo y Zaruma de la provincia de El Oro - Soto Romero, Yesenia Betsabe (2017)
The present thesis entitled "FEASIBILITY PROJECT FOR THE CREATION OF AN ORGANIC FERTILIZER PROCESSING COMPANY BASED ON CHICKEN BREED AND ITS MARKETING IN THE CANTONES BALSAS, MARCABELÍ, PIÑAS, PORTOVELO AND ZARUMA OF THE PROVINCE OF EL ORO" was carried out with the Purpose of encouraging organic agricultural production through the creation of a processing and marketing company of fertilizer based on chicken manure. In order to carry out the project, the deductive, descriptive, analytical and statistical method was used, as well as the different techniques that helped in the development and completion of the project. In the market study the potential demand was determined by all farmers (152), Real demand 133 farmers who use organic manure to strengthen their crops, during one year used 59,874 bags of 50Kilos the entire population of the real demand, in addition determined the effective demand with 57,479 bags of organic fertilizer of 50 kg, and 34,109 bags As unmet demand. The marketing plan highlights the presentation of the product (organic fertilizer based on 50 kg chicken manure, packed in plastic sachets, the sale price has a profit of 60% being distributed in the cantons of Balsas, Marcabelí, Piñas, Portovelo and Zaruma, the promotion of the product is proposed to be made through radio in the local press. The technical study indicates that the capacity to install is 27,360 sacks per year), the location of the processor will be in the Bellamaría Cantón Balsas parish, El Oro province, Coast region of the Republic of Ecuador, the physical infrastructure (covers for Waste collection, drying, warehouse and administrative office), machinery, tools, furniture and equipment, distribution of facilities, human resources. The production process describes all the steps and the grass flow of the process, points out the times and responsible ones. The processor will have a structural organization made up of partners, an administrative manager, legal adviser, secretary, accountant, production manager, three operators, sales manager and a salesman, for each work member is assigned their respective profile and job description For the position to be exercised. The legal constitution is proposed under the figure of limited liability company. In the economic study the budgets for fixed assets were determined $ 83.199,90 deferred assets $ 4018.35 and in current assets or working capital 28.833,77 Total investment amounts to $ 116,052 The financing is proposed to cover 66.052,02% (56,92) contribution of partners and 43,08% (50,000.00) of a loan managed by the National Development Bank, Whose debt would be paid in a term of 5 years, with a quarterly quota according to the amortization table. The total cost of operation in the first year is $ 121.800,75 in the third year $ 133.780,54 and for the fifth year $ 145.839,86 is spent between fixed and variable costs. The break-even point in terms of installed capacity for the first year is 46.87% and in terms of sales $ 91,337.06 and in the fifth year: depending on the installed capacity 45.88% and on the basis of sales $ 107,049.43 Cash flow was estimated for 5 years, according to net flows was calculated in NPV which resulted in $118.058,41 surpassing the initial investment, the internal rate of return 43,10% which exceeds 10% of the rate Interest ratio of the credit, the benefit ratio cost $ 1.60 obtaining a profit of 0.60 cents for every dollar invested and the recovery time is 2 years, 4 months and 14 days. In the sensitivity analysis it will be possible to increase costs to 27,35%, which gave 0.99 as a sensitivity index, otherwise they can decrease the revenue up to 17.10% with a sensitivity index of 0.99 So it is less than 1 and it is considered that the change does not affect the profitability of the project therefore is not sensitive. The conclusions mention the existence of demand and interest of farmers by the organic fertilizer, the distribution of the product directly, the technical alternatives provide the conditions to carry out the production process, the administrative structure establishes the organizational charts and functions And charge profiles, the investment valuation determines the amounts and sources of financing and the financial study demonstrates the feasibility of the investment project. The recommendations emphasize the use of the direct marketing channel, promote the product by radio wedges, properly distribute the facilities that favor the work, establish a good staff selection plan and lastly implement a budget control system for efficient monitoring Of costs and expenses.